2015
DOI: 10.1093/ehjcvp/pvv035
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular safety of anti-diabetic drugs

Abstract: Cardiovascular disease is the leading cause of morbidity and mortality among patients with diabetes, underscoring the importance of choosing anti-diabetic drugs that do not increase cardiovascular risk but might reduce the risk of cardiovascular events. Most type 2 diabetic patients die from cardiovascular causes despite the beneficial effects of blood pressure (BP) and lipid-lowering medications. The prevalence of patients with cardiovascular disease and diabetes mellitus is growing exponentially. Approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 114 publications
0
40
0
5
Order By: Relevance
“…Sulfonylureas act on pancreatic beta-cells, independently of serum glucose levels, to enhance insulin secretion, potentially causing adverse hypoglycemic events. This can prolong the QT interval and is associated with cardiac ischemia [19], increasing the risk of arrhythmias, acute MI, and sudden cardiac death [8]. A previous meta-analysis also reported a lower risk of hypoglycemia with SGLT2 inhibitors than with sulfonylureas [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfonylureas act on pancreatic beta-cells, independently of serum glucose levels, to enhance insulin secretion, potentially causing adverse hypoglycemic events. This can prolong the QT interval and is associated with cardiac ischemia [19], increasing the risk of arrhythmias, acute MI, and sudden cardiac death [8]. A previous meta-analysis also reported a lower risk of hypoglycemia with SGLT2 inhibitors than with sulfonylureas [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, most trials failed to demonstrate a reduction in the risk of cardiovascular mortality or morbidity, although these drugs were deemed safe [2,8]. The most recently reported randomized controlled trial (RCT), the Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients (EMPA-REG OUTCOME) trial, showed that SGLT2 inhibitor use decreases the risk of cardiovascular events, compared with placebo [9].…”
Section: Introductionmentioning
confidence: 99%
“…SGLT-2 inhibitors improve both glycemic and nonglycemic risk factors in T2DM patients. They induce urinary glucose losses around 40-80 g/day, resulting in decent glycemic control (HbA1c reduction around 0.7%) (42). This corresponds to around 200-300 kilocalories daily which can result in a 2-3 kg body weight loss over 24-52 weeks (40).…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
“…Mortality following hospitalization for HF is high, reaching 19.8% at 2.25 years in the control arm of a recent randomized HF trial [5]. Early treatment of hypertension has been shown to be effective in preventing hospitalization for HF in high-risk subjects [6]; however, intensive hypoglycemic therapy and a number of hypoglycemic agents may increase the risk of HF in diabetics, emphasizing the need for early identification of those at risk for HF and appropriate selection of hypoglycemic drugs [7,8]. Predictive models for death or HF based on clinical risk factors in heterogeneous populations have had only moderate success [9].…”
Section: Introductionmentioning
confidence: 99%